LENGTH-FREQUENCY DISTRIBUTION IN CYNOGLOSSUS SEMIFASCIATUS DAY ON THE WEST COAST DURING 1980-81 - Seshappa, G; Chakrapani, B K (Indian Journal of Fisheries, 2011)
In general, the seasonal length-frequency trends of Cynoglossus semifasciatiis showed a rough agreement with the past findings at Calicut, but with some differences. The pooled data of all the centres together showed the main mode at 10.5- 10.9 cm in May and 11.5-11.9 cm in October, the length range in the latter month being 8.4-16.4 cm, two smaller modes of May were represented by a single mode at 13-13.4 cm in October there being, however, other minor modes in both the months. New juveniles were seen in the catches in November and December, the motlal groups in the latter month being at 8-8.4 cm and 12-12.4 cm. The dominant higher size modes of four of the premonsoon months and also of October in the pooled data of 1980 were rather low as compared to the generalised trend of the earlier years of published work at Calicut. The cause for this apparent decline in the size of the mode is perhaps due to the large scale trawling during the past decade. The total length ranged from 6.35 cm to 16.4 cm taking all the samples together, the sample mean lengths ranging from 8.43 cm to 13.96 cm. The Standard Deviation (SD), Standard Error (SE) and the coefficient of Variation (CV) have also been worked out and tabulated. The total lengths of two samples from Cochin taken during January 1982 are also considered separately, in the tables.